Factors associated with commercial sexual activities among students engaging in casual heterosexual behaviors: a cross-sectional study in Zhejiang Province - Yang, Zhongrong; Ma, Qiaoqin; Chen, Weiyong; Chen, Wanjun; Zhou, Xin; Jiang, Tingting; Wang, Hui; Yao, Yaping (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the occurrence of and factors associated with commercial sexual activities among college students who engaged in casual heterosexual behaviors in the past year.MethodsUsing an independent self-designed online survey questionnaire, information on demographic characteristics, attitudes towards sex, HIV prevention and control knowledge, and intervention acceptance was collected. Logistic regression analysis was used to determine factors associated with commercial sexual behavior among college students who had engaged in casual heterosexual behavior in the past year.ResultsIn total, 42,380 students were surveyed and 440 incomplete questionnaires were excluded, resulting in 41,940 valid responses. Among them, 2,581 college students reported involvement in heterosexual activities in the previous year, representing 6.15% of the total student population. Specifically, 425 college students reported engaging in casual heterosexual behavior in the previous year, accounting for 16.5% of students who engaged in heterosexual activities. Of these, 74 (17.4%) students had engaged in commercial sex (average age, 19.99 ± 1.22 years). Multivariate logistic regression analysis indicated that accepting commercial sex [adjusted odds ratio (aOR) 7.33, 95% confidence interval (CI) 3.24–16.58], opposite-sex partners being non-students (aOR2.48, 95% CI 1.24–4.99), recent anal intercourse (aOR3.11, 95% CI 1.33–7.28), seeking casual partners on the Internet rather than offline (aOR2.33, 95% CI 1.19–4.56), perceived risk of HIV infection (aOR2.93, 95% CI 1.13–7.59), and consistent condom use during casual sex (aOR0.27, 95% CI0.12–0.65) or sometimes/often use (aOR0.26, 95% CI0.11–0.64) compared with never using a condom were independent factors associated with the occurrence of commercial sex among college students who had engaged in casual heterosexual behaviors in the past year.ConclusionCommercial sexual activity among college students who engaged in casual heterosexual behavior was relatively common in Zhejiang Province, and was characterized with a high degree of openness towards sex, a low perception of HIV risk, low condom usage, and knowledge-practice separation. Strengthening HIV risk warnings and sex education tailored to this group is recommended, to promote the integration of knowledge and action, increase condom usage rates, and reduce the occurrence of unsafe sexual behavior.